1994
DOI: 10.1080/11250009409355870
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotactile and olfactory antennal sensilla in four species of female tabanids (Diptera)

Abstract: This paper reports the loci, structure and numerical distribution of various types of mechanotactile and olfactory sensilla in four species of female tabanids, i.e., Tabanus rubidus, Tabanus striatus, Haematopota dissimilis, and Tabanus subcinerences. It was observed that sensilla chaetica were confined to scape and pedicel, while sensilla basiconica were confined to the first segment of flagellum. Sensilla trichoidea and sensilla stellate were distributed over all the segments of flagellum in all four species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 8 publications
4
18
0
Order By: Relevance
“…The indifferent electrode was inserted into the pedicel of the antenna and the recording electrode was brought into contact with the distal end of the flagellum. The majority of olfactory sensilla (described in females of four species of tabanid) are present on the first segment of the flagellum (Parashar et al , 1994). Furthermore, previous electrophysiological experiments have shown the presence of gustatory chemosensilla at the tip of the tabanid antennae (Stoffolano et al , 1990).…”
mentioning
confidence: 99%
“…The indifferent electrode was inserted into the pedicel of the antenna and the recording electrode was brought into contact with the distal end of the flagellum. The majority of olfactory sensilla (described in females of four species of tabanid) are present on the first segment of the flagellum (Parashar et al , 1994). Furthermore, previous electrophysiological experiments have shown the presence of gustatory chemosensilla at the tip of the tabanid antennae (Stoffolano et al , 1990).…”
mentioning
confidence: 99%
“…In C. lee-tularius the former are represented by a smooth peg and the latter by a grooved sensilla. Further, Parashar et al (1994) reported different types of sensilla basiconica in four different species of Tabanus which have not been observed in C. hemipterus. The presence of such types of sensilla basiconica may be related to olfaction, as flying haematophagous species have to reach their hosts from a long distance.…”
Section: Sensilla Basiconicamentioning
confidence: 93%
“…The presence of serrated grooved bristles was predominantly observed in the allied species C. lectularius by Streinbrecht & Muller (1976). However, this type of sensilla has not been reported from haematophagous flies (Parashar et al, 1994) and neither from non-haematophagous insects like Periplaneta americana and Supella longipalpa (Prakash et al, 1992(Prakash et al, , 1995. Streinbrecht & Muller (1976) reported that in serrated grooved bristles and grooved bristles, the fine structure of sensory ending closely resembles that of other mechanoreceptor bristles.…”
Section: Sensilla Basiconicamentioning
confidence: 99%
“…Representatives of a number of major insect orders have been studied, including Orthoptera (Yokohari & Tateda, 1976;Chapman & Greenwood, 1986;Bland & Rentz, 1994;Prakash et al, 1995), Hymenoptera (Gupta, 1992), Diptera (Been, et al, 1988;Ross, 1992;Parashar et al, 1994;Giangiuliani et al, 1994), Hemiptera (Catala & Schofield, 1994) and Plecoptera (Kapoor, 1985). Representatives of a number of major insect orders have been studied, including Orthoptera (Yokohari & Tateda, 1976;Chapman & Greenwood, 1986;Bland & Rentz, 1994;Prakash et al, 1995), Hymenoptera (Gupta, 1992), Diptera (Been, et al, 1988;Ross, 1992;Parashar et al, 1994;Giangiuliani et al, 1994), Hemiptera (Catala & Schofield, 1994) and Plecoptera (Kapoor, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The primary method by which insect receptors have been examined has been high-vacuum scanning electron microscopy, involving prior sputter-coating of specimens with gold or gold-palladium. Representatives of a number of major insect orders have been studied, including Orthoptera (Yokohari & Tateda, 1976;Chapman & Greenwood, 1986;Bland & Rentz, 1994;Prakash et al, 1995), Hymenoptera (Gupta, 1992), Diptera (Been, et al, 1988;Ross, 1992;Parashar et al, 1994;Giangiuliani et al, 1994), Hemiptera (Catala & Schofield, 1994) and Plecoptera (Kapoor, 1985). Scans of the sensilla of Coleoptera have included comparative analyses of particular structures, such as digitiform sensilla, across a range of families (Honomichl, 1980;Honomichl & Guse, 1981), or detailed studies of the structures found on the palps and/or antennae of individual species within, for example, the Coccinellidae (Fischer & Kogan, 1986;Jourdan et al, 1995), Scolytidae (Hallberg, 1982;Faucheux, 1994), Chrysomelidae (Ritcey & McIver, 1990), Curculionidae (Bland, 1981) and Tenebrionidae (Harbach & Larsen, 1977).…”
Section: Introductionmentioning
confidence: 99%